2005
DOI: 10.1007/s11187-004-6483-y
|View full text |Cite
|
Sign up to set email alerts
|

Loan Repayment Performance in Community Development Finance Institutions in the UK

Abstract: This paper identifies the key institutional factors that influence loan loss rates in Community Development Finance Institutions in the UK. Traditional bank credit assessment puts the blame of poor loan performance largely on the borrower. This is the first study of its kind to examine institutional characteristics of 16 CDFIs in the UK and assess their influence on the loan loss rates. The results show that 8 out of the 13 institutional characteristics examined significantly influence loan repayment performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 7 publications
2
50
0
1
Order By: Relevance
“…The predictor variables were chosen according to their importance to the repayment process. Results of many studies investigating repayment performance considered these factors critical in determining the credit agency's repayment performance level (Yasir et al, 2012;Greenbaum & Thakor, 1995;Hulme & Mosley, 1996;Derban et al, 2005). The variables considered in our study include the volume of loans borrowed from the ACC (X1); the volume of loans repaid to the ACC including ACC profits (X2); the number of borrowers (X3); the number of ACC staff members (X4), the borrower's age (X5), and the borrowers' farming experience (X6).…”
Section: Analytical Frameworkmentioning
confidence: 99%
“…The predictor variables were chosen according to their importance to the repayment process. Results of many studies investigating repayment performance considered these factors critical in determining the credit agency's repayment performance level (Yasir et al, 2012;Greenbaum & Thakor, 1995;Hulme & Mosley, 1996;Derban et al, 2005). The variables considered in our study include the volume of loans borrowed from the ACC (X1); the volume of loans repaid to the ACC including ACC profits (X2); the number of borrowers (X3); the number of ACC staff members (X4), the borrower's age (X5), and the borrowers' farming experience (X6).…”
Section: Analytical Frameworkmentioning
confidence: 99%
“…Nicholls (2010) notes that despite growing international policy interest in social investment, with the development of a considerable and fast growing grey literature (Bank of England 2003;HM Government 2011;Carrington 2005;J.P.Morgan 2010;Monitor Institute 2011), it has failed to attract much academic analysis or research. Exceptions to this include Nicholls' own work (Nicholls 2009; which has sought to conceptualise the social investment field and better define social entrepreneurship, community finance including institutional measures (GHK 2010;Affleck and Mellor 2006;Derban et al 2005;Pollinger et al 2007), the financial exclusion of businesses and individuals (Fuller and Mellor 2008), and the measurement of social and financial returns (Nicholls 2009;Arvidson et al 2011). Indeed, the fluidity and general pace of change around social investment has probably hampered the emergence of a body of academic research.…”
Section: The Emergence Of Social Investment and The Policy Responsementioning
confidence: 99%
“…They applied a comparative analysis of the determinants of the repayment performance and of loan size to make policy recommendations on the allocation of loans by MFIs. Derban et al (2005) investigated loan repayment performance in community development finance institutions in the UK. They reported that 8 out of the 13 institutional characteristics examined substantially influence loan repayment performance.…”
Section: Introductionmentioning
confidence: 99%